An undergraduate experiment demonstrating the physics of metamaterials with acoustic waves and soda cans - Wilkinson,JT; Whitehouse,CB; Oulton,RF; Gennaro,SD (American Journal of Physics, 2016)
We describe a novel undergraduate research project that highlights the physics of metamaterials withacoustic waves and soda cans. We confirm the Helmholtz resonance nature of a single can bymeasuring its amplitude and phase response to a sound wave. Arranging multiple cans in arrayssmaller than the wavelength, we then design an antenna that redirects sound into a preferred direction.The antenna can be thought of as a new resonator, composed of artificially engineered meta-atoms,similar to a metamaterial. These experiments are illustrative, tactile, and open ended so as to enablestudents to explore the physics of matter/wave interaction